Applying Islamic Economic Law in Productive Zakat Management A Case Study of Amil Zakat Institutions in Indonesia - Susandi, Adi; Sunaryo Mukhlas, Oyo (Zona Law And Public Administration Indonesia, 2025)
This study explores the application of Islamic economic law in the management of productive zakat by Amil Zakat Institutions in Indonesia. The research aims to analyze how legal principles derived from Islamic jurisprudence (fiqh muamalah) are implemented in real-world zakat programs designed to empower the poor through sustainable economic activities. Using a qualitative case study method, data were collected from institutional reports, interviews with zakat officers, and documentation of program outcomes. The findings show that while most institutions adhere to core legal frameworks such as DSN-MUI fatwas and national zakat regulations, there remain gaps in contract standardization, post-disbursement supervision, and alignment with maqashid sharia. Some programs emphasize legal compliance but neglect social impact, highlighting a form over substance tendency. The study recommends integrating maqashid sharia principles and participatory development approaches to enhance both the legal validity and socio-economic effectiveness of productive zakat. These insights contribute to the development of sharia-compliant governance and support innovation in Islamic philanthropic management